Employment, occupational mobility and earnings of women in the Kuching Urban Labour Market / Low Kuek Long … [et.al.] - Long, Low Kuek; Ching, Goy Siew; Lob, Abdul Jalil; Suhaimi, Rosita (2003)
In Malaysia, research pertaining to the employment status and earnings of women has been scanty and often not readily available to the public and women themselves. This study was therefore conceptualized to fill the gap, by looking at the urban women workers in the manufacturing sector in Kuching. Three aspects of women status i.e.memployment structure, pattern of occupational mobility and earnings of women vis-a-vis earnings ofmen were examined through a questionnaire survey.